Simplified analysis of iron loss in three‐phase transformer considering rotating loss. Issue 1 (2014) - ,; ,; ,; ,
Abstract : Purpose – A simplified method for calculating iron loss of three‐phase transformer is proposed in this paper. The rotating iron loss measured from 2‐D vector magnetic property measurement system of gain‐oriented silicon steel sheet can be taken into account in this method. The paper aims to discuss these issues.Design/methodology/approach – The finite element analysis formulation is combined with the magnetic reluctivity model expressed by diagonal tensor for 2‐D nonlinear and anisotropic magnetic problem, while the iron loss is computed in terms of the interpolation of rotational loss curves measured under various loci of controlled magnetic flux density B.Findings – The iron loss of three‐phase transformer is obtained by the proposed method. And the calculating iron loss is verified with experimental results.Originality/value – The method presented in this paper enables the iron loss of three‐phase transformer to be more accurately calculated and more easily applied, considering the rotational iron loss.